Comparison Between Progesterone Rise In Fresh Cycles Versus Frozen Cycles (Journal of Pharmaceutical Negative Results, 2023)
The impact of elevated progesterone levels that affects the quality of the oocyte or resulting embryo is still unclear and the increase of progesterone likely constrains the endometrium, causing an asynchrony between the developing embryo and the endometrial receptivity. So we aimed in this review to discuss the effect of high progesterone level at day of HCG injection that affect the pregnancy rate on frozen cycles undergoing the intracytoplasmic sperm injection (ICSI) treatment versus fresh cycles.